Evaluation and Treatment of Cardiac Tamponade in a Pregnant Patient. (16th January 2020) - Romagano, Matthew P.; Patel, Krunal; Williams, Shauna; Apuzzio, Joseph J.
Abstract : Cardiac tamponade is an uncommon but life-threatening emergency that may occur in pregnant women. There is a plethora of causes, but prompt diagnosis and intervention is imperative to optimize both maternal and fetal outcomes. We report on a case of a large pericardial effusion leading to cardiac tamponade occurring in the 32 nd week of gestation in a previously healthy woman. Rapid recognition and a multidisciplinary team meeting resulted in a therapeutic pericardial window and drainage and relief of symptoms. The woman underwent an uncomplicated repeat cesarean delivery at term with a positive neonatal outcome. This case highlights the importance of a rapid diagnosis and a team-based approach to managing a complex medical condition like cardiac tamponade in pregnancy.